2006
DOI: 10.1055/s-0037-1617084
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation management during liver transplantation

Abstract: SummaryIn the course of liver transplantation many patients develop coagulation and bleeding disorders. On the other hand, some patients suffer thromboembolic events in the perioperative period with sometimes fatal outcome. For this reason, in 1999 we changed our coagulation management for liver transplantation and abolished the routine prophylaxis with antifibrinolytic drugs. In this context we implemented the ROTEM® system (Pentapharm GmbH, Munich) in our perioperative point-of-care coagulation management.Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(128 citation statements)
references
References 67 publications
3
119
0
6
Order By: Relevance
“…The value of ROTEM has also been reported for cardiac surgery and liver transplantations 6,7,17 , where it is particularly important to be able to monitor the coagulation in real time. Unfortunately, such real-time monitoring is not feasible with standard laboratory coagulation tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of ROTEM has also been reported for cardiac surgery and liver transplantations 6,7,17 , where it is particularly important to be able to monitor the coagulation in real time. Unfortunately, such real-time monitoring is not feasible with standard laboratory coagulation tests.…”
Section: Discussionmentioning
confidence: 99%
“…It can be used in the laboratory or at the patient bedside. [6][7][8][9] We recently showed ª 2009 The Authors Journal compilation ª RCOG 2009 BJOG An International Journal of Obstetrics and Gynaecology that the ROTEM system allows the detection of hypercoagulation linked to pregnancy. We also showed that ROTEM gives a reliable and rapid assessment of coagulation during normal pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Görlinger [79] developed and implemented a ROTEM based point of care (POC) algorithm for LT to guide response to clearly defined abnormal ROTEM parameters. A POC algorithm with first line use of factor concentrates applied to a variety of clinical contexts (trauma, cardiac, transplant and critical care) in three major teaching hospitals in Germany and Austria was associated with an impressive 90% reduction in FFP use, 72% reduction in platelet use, 62% reduction in RBC use and 50% reduction in incidence of massive transfusion and increased use of factor concentrates [80] .…”
Section: Measurement Of Teg Functional Fibrinogen (Teg Ff)mentioning
confidence: 99%
“…POC-guided transfusion was associated with decreased transfusion of frozen plasma (12.8 ± 7 vs. 21.5 ± 1 2.7 units), but did not aff ect 3-year survival [16]. Analyzing more than 18, 000 thromboelastography measurements in the context of 642 patients with liver transplantation, the implementation of a POC coagu lation management based on early, calculated, goaldirected therapy with fi brinogen concentrate, prothrombin complex concentrate and antifi brinolytic therapy resulted in early detection of hyperfi brinolysis and consequently antifi brinolytic therapy [17], and a reduction in transfusion requirements for erythrocytes, fresh frozen plasma (FFP), and platelets as well as a reduced incidence of massive transfusion [18].…”
Section: Organ Transplantationmentioning
confidence: 99%